2020
DOI: 10.1128/msystems.00534-20
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Phage Butters-Encoded Proteins Contribute to Host Defense against Viral Attack

Abstract: Many sequenced bacterial genomes, including those of pathogenic bacteria, contain prophages. Some prophages encode defense systems that protect their bacterial host against heterotypic viral attack. Understanding the mechanisms undergirding these defense systems is crucial to appreciate the scope of bacterial immunity against viral infections and will be critical for better implementation of phage therapy that would require evasion of these defenses. Furthermore, such knowledge of prophage-encoded defense mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Homologs from phages Sbash, CarolAnn, and Butters confer a broad viral defense that mirrors the Rex exclusion behavior in λ (Gentile et al, 2019;Mageeney et al, 2020;Montgomery et al, 2019). These genes are organized in tandem in a single operon that is often directly adjacent to a CI-like repressor gene, raising the tantalizing possibility that other bacterial viruses also use these analogous systems to fine tune the balance between lysogeny and lytic growth.…”
Section: Lysogenic State Lytic Statementioning
confidence: 99%
“…Homologs from phages Sbash, CarolAnn, and Butters confer a broad viral defense that mirrors the Rex exclusion behavior in λ (Gentile et al, 2019;Mageeney et al, 2020;Montgomery et al, 2019). These genes are organized in tandem in a single operon that is often directly adjacent to a CI-like repressor gene, raising the tantalizing possibility that other bacterial viruses also use these analogous systems to fine tune the balance between lysogeny and lytic growth.…”
Section: Lysogenic State Lytic Statementioning
confidence: 99%
“…Soils are intrinsically diverse partially due to their wide compositional spectrum and spatial heterogeneity in terms of physicochemical properties 1 , supporting a high diversity of interacting microbes that are pivotal to ecosystem services including global C and N biogeochemical cycles 2 . Viruses are extremely abundant and diverse biological entities on earth, playing vital roles in affecting soil microbiota and functions 3,4 via regulating microbial community dynamics 5 , reprogramming host metabolism during infection 6,7 , and serving as vectors of horizontal gene transfer 3 . Viral metagenomics has greatly expanded the viral ecology of aquatic ecosystems 8,9 and mammalian guts 10,11 , knowledge about soil viruses lags behind.…”
mentioning
confidence: 99%
“…Previous genetic studies identified rex- like genes in the temperate Actinobacteriophages Sbash, CarolAnn, and Butters that function as exclusion systems and provide broad defense activity to prevent superinfection by other viruses (8587). An extensive BLAST search of the Actinobacteriophage Database (36) revealed additional Rex homologs in phages DumpsterDude, Toast, Rubeelu, Blino, and PCoral7 ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%